Privacy and Security for Cloud Computing - Pearson, Siani; Yee, George (Computer Communications and Networks,, 2013)
Despite the enormous potential of cloud computing, consumer uncertainty and concern regarding issues of privacy, security and trust remain a major barrier to the switch to cloud models. This comprehensive and authoritative text/reference provides an in-depth analysis of the latest advances in privacy, security and risk technologies within cloud environments. Containing contributions from leading experts in the field, the text presents both a thorough introduction to the core issues, and a practical selection of innovative solutions to common problems. A Glossary is also included at the end of the book. Topics and features: Considers the various forensic challenges for legal access to data in a cloud computing environment Discusses privacy impact assessments for the cloud, and examines the use of cloud audits to attenuate cloud security problems Reviews conceptual issues, basic requirements and practical suggestions for provisioning dynamically configured access control services in the cloud Proposes scoped invariants as a primitive for analyzing a cloud server for its integrity properties Investigates the applicability of existing controls for mitigating information security risks to cloud computing environments Describes risk management for cloud computing from an enterprise perspective This pioneering volume is essential reading for business professionals, students and researchers interested in the field of privacy and security protection for the cloud, and/or complex service provisioning. Newcomers to these areas will benefit from the solid overview of the field, whereas established experts will value the novel, cutting-edge research described in the work.